Flow batteries with solid energy boosters - Yuriy Tolmachev; Svetlana V. Starodubceva (Journal of Electrochemical Science and Engineering, 2022)
Adding solid electroactive materials as energy boosters to flow battery tanks provides a path to electrical energy storing systems with unprecedently high specific energy and specific power, that can solve the needs of both automotive and stationary energy storage markets. This work reviews the physical and chemical principles behind this new class of flow batteries, the history of this technology, and the most promising research directions.